Ajwa Date (Phoenix dactylifera L.) Extract Inhibits Human Breast Adenocarcinoma (MCF7) Cells In Vitro by Inducing Apoptosis and Cell Cycle Arrest - Khan, Fazal (PLoS One, 2016)
INTRODUCTION: Phoenix dactylifera L (Date palm) is a native plant of the Kingdom of Saudi Arabia (KSA) and other Middle Eastern countries. Ajwa date has been described in the traditional and alternative medicine to provide several health benefits including anticholesteremic, antioxidant, hepatoprotective and anticancer effects, but most remains to be scientifically validated. Herein, we evaluated the anticancer effects of the Methanolic Extract of Ajwa Date (MEAD) on human breast adenocarcinoma (MCF7) cells in vitro. METHODS: MCF7 cells were treated with various concentrations (5, 10, 15, 20 and 25 mg/ml) of MEAD for 24, 48 and 72 h and changes in cell morphology, cell cycle, apoptosis related protein and gene expression were studied. RESULTS: Phase contrast microscopy showed various morphological changes such as cell shrinkage, vacuolation, blebbing and fragmentation. MTT (2-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay demonstrated statistically significant dose-dependent inhibitions of MCF7 cell proliferation from 35% to 95%. Annexin V-FITC and TUNEL assays showed positive staining for apoptosis of MCF7 cells treated with MEAD (15 mg and 25 mg for 48 h). Flow cytometric analyses of MCF7 cells with MEAD (15 mg/ml and 20 mg/ml) for 24 h demonstrated cell cycle arrest at 'S' phase; increased p53, Bax protein expression; caspase 3activation and decreased the mitochondrial membrane potential (MMP). Quantitative real time PCR (qRT-PCR) analysis showed up-regulation of p53, Bax, Fas, and FasL and down-regulation of Bcl-2. CONCLUSIONS: MEAD inhibited MCF7 cells in vitro by the inducing cell cycle arrest and apoptosis. Our results indicate the anticancer effects of Ajwa dates, which therefore may be used as an adjunct therapy with conventional chemotherapeutics to achieve a synergistic effect against breast cancer.